1996
DOI: 10.1152/ajprenal.1996.271.2.f414
|View full text |Cite
|
Sign up to set email alerts
|

Long-term regulation of four renal aquaporins in rats

Abstract: The aquaporins are molecular water channels expressed in the kidney and other organs. To investigate long-term regulation of renal expression of these water channels, we carried out immunoblotting studies using membrane fractions from rat renal cortex and medulla. Both 48-h water restriction in Sprague-Dawley rats and 5-day arginine vasopressin (AVP) infusion in Brattleboro rats caused significant increases in the expression levels of two aquaporins, aquaporin-2 and aquaporin-3, while the levels of aquaporin-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

31
389
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 304 publications
(424 citation statements)
references
References 28 publications
31
389
4
Order By: Relevance
“…In fact, they are different. In the case of UT-A1, chronic dDAVP infusion did not induce a change in mRNA and protein expression in whole IM [31,37] in contrast to the considerable increase seen in diabetes mellitus (present study). A recent study showed that chronic dDAVP infusion induced a shift of UT-A1 protein from the tip to the base of IM [38].…”
Section: Discussioncontrasting
confidence: 65%
See 4 more Smart Citations
“…In fact, they are different. In the case of UT-A1, chronic dDAVP infusion did not induce a change in mRNA and protein expression in whole IM [31,37] in contrast to the considerable increase seen in diabetes mellitus (present study). A recent study showed that chronic dDAVP infusion induced a shift of UT-A1 protein from the tip to the base of IM [38].…”
Section: Discussioncontrasting
confidence: 65%
“…The 117000 M r protein was greatly increased in both IM base and tip and thus in both initial and terminal IMCD. Such an increase in the 117000 M r band has been reported for total inner medulla in several cases of high urine flow rate (furosemide treatment, Brattleboro rats with diabetes insipidus, low protein diet [31]). …”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations